The Correlation between Working Memory Capacity and Grade Point Average of Medical Students Batch 2012 Faculty of Medicine Sebelas Maret University - Itqan Ghazali; . Santoso; . Hardjono (Nexus Kedokteran Komunitas, 2015)
Background: Learning achievement is an indicator of success in learning process. There are 3 17% of college students who have difficulty in learning that caused them to have low learning achievement. As one of cognitive ability, working memory is the major factor that affects learning achievement. Level of working memory affects someones ability to learn subjects, understand text book and solve problems in exam. Student with low working memory capacity mostly has poor learning achievement, hard to focus on teachers explanation and easily forget the instructions in learning process. Methods: This research is an observational analytic study with cross sectional approach. It was done in Faculty of Medicine Sebelas Maret University, Surakarta. Samples were students with age more than 16 years-old, Body Mass Index more than 17, never experiencing heavy head trauma, not having chronic disease, and were willing to be respondent and approved the informed consent. Sampling was done by purposive sampling method after selected based on inclusion and exclusion criteria. Result: Fifty five students were included in the study, 4 students (7.27%) with low working memory capacity and low GPA, 2 students (3.64%) with low working memory and high GPA, 21 students (38.18%) with high working memory capacity and low GPA, 28 students (50.91%) others were students with high working memory capacity and high GPA. Result shown p = 0.269 (p > 0.05) from data analysis with significance number ? = 0.05 and Odds Ratio (OR) value = 2.67. Conclusion: There was no significant correlation between working memory capacity and GPA of medical student batch 2012 Faculty of Medicine Sebelas Maret University. Keyword: Working Memory Capacity, GPA, Learning Achievement, Medical Student.